Cone-Beam Computed Tomography Study of Root and Canal Morphology of Mandibular First and Second Premolars in Nepalese Population - Snigdha Shubham,; Kriti Shrestha,; Sageer Ahmad,; Vanita Gautam,; Vaibhav Rai, (Journal of Universal College of Medical Sciences, 2024)
INTRODUCTIONMandibular premolars are challenging to treat endodontically due to their varied root and canal morphology, impacting treatment prognosis. This study aimed to assess the root and canal morphology of mandibular premolars in a Nepali subpopulation using Cone Beam Computed Tomography (CBCT) imagesMATERIAL AND METHODSA descriptive cross-sectional study was conducted on 348 untreated mandibular ﬁrst and second premolars teeth of both right and left side having completely developed roots from 87 CBCT images of patients from September 2021-April 2024. The study assessed the number of roots, root canals, their conﬁgurations and the tooth length.RESULTSSigniﬁcant variations in root morphology were observed in mandibular premolars, with most having one root (91.40% in ﬁrst premolars, 100% in  second premolars) and  one  canal (50% in  ﬁrst  premolars, 70.69% in  second premolars). Type I conﬁgurations were most common (50% in ﬁrst premolars, 70.69% in second premolars), followed by Type V (21.26% in ﬁrst premolars, 13.79% in second premolars). C-shaped canals were more frequent in ﬁrst premolars (2.3%) than second premolars (1.15%).CONCLUSIONThis study provides valuable insights into root canal morphology variations of mandibular premolars in Nepalese sub population. The ﬁndings can help clinicians better understand importance CBCT's in anatomical variations and improve endodontic diagnosis and treatment planning for better outcomes.